Activation of the mitogen-activated protein kinase cascade by pertussis toxin-sensitive and -insensitive pathways in cultured ventricular cardiomyocytes. - Bogoyevitch, M A (1995)
The involvement of pertussis toxin (PTX)-sensitive and -insensitive pathways in the activation of the mitogen-activated protein kinase (MAPK) cascade was examined in ventricular cardiomyocytes cultured from neonatal rats. A number of agonists that activate heterotrimeric G-protein-coupled receptors stimulated MAPK activity after exposure for 5 min. These included foetal calf serum (FCS), endothelin-1 (these two being the most effective of the agonists examined), phenylephrine, endothelin-3, lysophosphatidic acid, carbachol, isoprenaline and angiotensin II. Activation of MAPK and MAPK kinase (MEK) by carbachol returned to control levels within 30-60 min, whereas activation by FCS was more sustained. FPLC on Mono Q showed that carbachol and FCS activated two peaks of MEK and two peaks of MAPK (p42MAPK and p44MAPK). Pretreatment of cells with PTX for 24 h inhibited the activation of MAPK by carbachol, FCS and lysophosphatidic acid, but not that by endothelin-1, phenylephrine or isoprenaline. Involvement of G-proteins in the activation of the cardiac MAPK cascade was demonstrated by the sustained (PTX-insensitive) activation of MAPK (and MEK) after exposure of cells to AlF4-. AlF4- activated PtdIns hydrolysis, as did endothelin-1, endothelin-3, phenylephrine and FCS. In contrast, the effect of lysophosphatidic acid on PtdIns hydrolysis was small and carbachol was without significant effect even after prolonged exposure. We conclude that PTX-sensitive (i.e. Gi/G(o)-linked) and PTX-insensitive (i.e. Gq/Gs-linked) pathways of MAPK activation exist in neonatal ventricular myocytes. FCS may stimulate the MAPK cascade through both pathways.